Surnames in modern Russia - Valeriy Yumaguzin; Maria Vinnik (Taylor & Francis Group, 2019)
Background: Previous studies on Russian surnames have been based on outdated and inconsistent sources; they also had limited territorial coverage and population samples constrained by Russian ethnicity. Aim: To study surnames for the present Russian population, including migrants, as of January 2019. Subjects and methods: Based on cell phone subscriber data, our sample has twenty nine million people and 380 thousand different surnames. Results: We made a list of five hundred of the most popular surnames in modern Russia, and the top five surnames in several regions. Ivanov is the most common surname in Russia. Kuznetsov, Smirnov, Popov, and Petrov contribute to the top five most popular surnames. Thirty-one percent of the names listed are of non-Russian origin: Arabian, Turkic, Ukrainian, Armenian, Jewish, Chinese and Korean surnames are among them. There is a core of fourteen thousand surnames, which are used by 70% of the population. The regions with a high variety of surnames are located within the main belt of settlement in Russia, which fostered a more active exchange of the population. Conclusions: The regional surname distribution reflects the specificity of historical pathways of settlement and ethnic, cultural and religious plurality.